Efektivitas Penggunaan Teknologi Informasi Dalam Pembelajaran PAI Terhadap Motivasi Belajar Peserta Didik - Ujang Supyandi (PT Alahyan Publisher Sukabumi, 2025)
The importance of information technology in improving the quality of education, especially in attracting students' interest and motivation to learn which is often influenced by monotonous conventional learning methods. The purpose of this study is to analyze the use of information technology in PAI and assess its impact on students' learning motivation. The research method used is qualitative with a descriptive approach. Data collection was carried out through observation, interviews, and documentation, involving PAI educators, principals, and students. The data obtained was systematically analyzed to find relevant patterns and themes. The results show that the application of information technology, such as laptops, LCD projectors, and multimedia applications, significantly increases the effectiveness of PAI learning. Students become more active, motivated, and show improvement in understanding the subject matter. Although there are variations in motivation among students, the use of information technology has been proven to be able to create a more interactive and fun learning atmosphere. This study recommends that school management continue to improve technology facilities and train educators in their use to achieve better learning outcomes.